Tata Kelola Badan Layanan Umum di Perguruan Tinggi Keagamaan Islam Negeri Berbasis Good Governance - Novardy (JURNAL ILMIAH GEMA PERENCANA, 2025)
This Policy Paper describes the policy of the Public Service Agency (BLU) at State Islamic Religious Colleges (PTKIN) as mandated in the Regulation of the Minister of Finance Number 129/PMK.05/2020 of 2020 concerning Guidelines for the Management of Public Service Agencies, which aims to improve autonomy, efficiency, and quality of education services. The purpose of this policy analysis is expected to contribute to the development of a more effective BLU management policy at PTKIN. This paper uses a qualitative writing method with an approach to descriptive analysis of various data sources related to the BLU implementation policy at PTKIN. The results show that implementing the BLU policy at PTKIN has brought significant changes in the management of higher education. However, the implementation of this policy faces various challenges, such as changes in organizational culture, limited human resources, difficulties in adapting competitive business models, limited infrastructure, and regulatory complexity. This study analyzes these challenges and proposes several alternative innovative solutions, such as strengthening governance, increasing HR capacity, diversifying revenue sources, developing research-based business models, utilizing digital technology, and enhancing cooperation with industry. It is hoped that these efforts will provide the widest possible positive impact on prosperity in institutional transformation in higher education, which will continuously give rise to improvements in the quality of public services.